Retinoid X receptor alpha forms tetramers in solution. - Kersten, S (1995)
Protein-protein interactions allow the retinoid X receptor (RXR) to bind to cognate DNA as a homo- or a heterodimer and to participate in mediating the effects of a variety of hormones on gene transcription. Here we report a systematic study of the oligomeric state of RXR in the absence of a DNA template. We have used electrophoresis under nondenaturing conditions and chemical crosslinking to show that in solution, RXR alpha forms homodimers as well as homotetramers. The dissociation constants governing dimer and tetramer formation were estimated by fluorescence anisotropy studies. The results indicate that RXR tetramers are formed with a high affinity and that at protein concentrations higher than about 70 nM, tetramers will constitute the predominant species. Tetramer formation may provide an additional level of the regulation of gene transcription mediated by RXRs.